2017
DOI: 10.3389/fneur.2017.00336
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Mediating both Excitatory and Inhibitory Effects in a Rat Model of Meningeal Nociception and Headache Generation

Abstract: Background/purposeHydrogen sulfide (H2S) is a neuromodulator acting through nitroxyl (HNO) when it reacts with nitric oxide (NO). HNO activates transient receptor potential channels of the ankyrin type 1 (TRPA1) causing release of calcitonin gene-related peptide from primary afferents. Activation of meningeal nociceptors projecting to the human spinal trigeminal nucleus (STN) may lead to headaches. In a rat model of meningeal nociception, the activity of spinal trigeminal neurons was used as read-out for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
0
18
1
1
Order By: Relevance
“…This receptor channel can also be activated by volatile constituents such as umbellulone of the "headache tree" (Nassini et al 2012). Its functional role in trigeminal nociception is controversial, because on one hand there is experimental evidence for a cooperative effects with TRPV1 in meningeal afferents (Denner et al 2016) but on the other hand for a dual nociceptive-antinociceptive effect when recordings were made from spinal trigeminal neurons (Teicher et al 2017). In addition, TRP channels of the M8 type (TRPM8) are expressed in trigeminal ganglion neurons.…”
Section: Receptors For Other Signal Molecules Expressed In the Trigemmentioning
confidence: 99%
“…This receptor channel can also be activated by volatile constituents such as umbellulone of the "headache tree" (Nassini et al 2012). Its functional role in trigeminal nociception is controversial, because on one hand there is experimental evidence for a cooperative effects with TRPV1 in meningeal afferents (Denner et al 2016) but on the other hand for a dual nociceptive-antinociceptive effect when recordings were made from spinal trigeminal neurons (Teicher et al 2017). In addition, TRP channels of the M8 type (TRPM8) are expressed in trigeminal ganglion neurons.…”
Section: Receptors For Other Signal Molecules Expressed In the Trigemmentioning
confidence: 99%
“…A functional role of HNO in elevated dura skin blood flow, as well as its effect on murine BP was demonstrated by Eberhardt and colleagues in very elegant experiments. They also detected CGRP release in response to HNO from various tissues including murine heart, mesentery, sciatic nerve and rat dura (Eberhardt et al ., ; Wild et al ., ; Dux et al ., ; Miyamoto et al ., ; Teicher et al ., ). Interaction of inorganic polysulfide with TRPA1 ion channels was examined in RIN14B, HEK293, chicken thoracic aorta epitheloid cells and murine DRG neurons.…”
Section: Effects Of Sulfur Species Mediated By Trpa1 Channelsmentioning
confidence: 97%
“…TRPA1 can also be activated by volatile substances such as umbellulone of the "headache tree" [54]. Its functional role in trigeminal nociception is controversial, because there is experimental evidence for a cooperative effect with TRPV1 in meningeal afferents [55] but also for a dual nociceptive-antinociceptive effect when recordings were made from spinal trigeminal neurons [56], as discussed below in more detail (Figure 2). Another member of the TRP receptor family implicated in the migraine pathophysiology is the TRPM8 that is a cold-sensitive channel activated also by natural and synthetic "cooling" agents, such as menthol and icilin ( Figure 2).…”
Section: Expression Of Trpv1 and Trpa1 And Co-expression With Neuropementioning
confidence: 99%
“…These effects may be further modulated in afferent second order neurons. In a rat model of meningeal nociception, recordings from neurons in the spinal trigeminal nucleus with meningeal afferent input indicated that individual neurons may be activated or inhibited by the TRPA1 agonist nitroxyl (HNO, see below) [56]. Thus, the effects of TRPA1 agonists may depend on the site of action (peripheral vs. central terminals) and the functional characteristics of higher order neurons.…”
Section: Signals Sensitizing Trigeminal Nociceptors-involvement and Imentioning
confidence: 99%